2019
DOI: 10.1140/epje/i2019-11894-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of long flexible fibers in homogeneous isotropic turbulence

Abstract: We numerically investigated the transport, deformation and buckling events of an isolated elastic fiber in Taylor-Green vortices and studied the dynamics of long filaments in homogeneous isotropic turbulence. The fiber is modelled by an assembly of spherical beads. The contact between beads enforces the inextensibility of the filament while bending is accounted for by the Gears Bead Model (GBM) proposed by Delmotte et al. (2015). In the cellular Taylor-Green flow, the buckling probability is a function of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The problem also bears an important aspect of fluid mechanics that relates the rotational dynamics of anisotropic particles to the velocity gradient tensor in turbulence [4]. Although most studies to date have primarily focused on the dynamics of rigid particles smaller than the Kolmogorov length (η) [4,[11][12][13], some have extended this interest to rigid inertial fibers [5][6][7]9,10] as well as to flexible fibers [14][15][16][17][18][19]. Previous theoretical and numerical studies on inertialess fibers shorter than the Kolmogorov length η have shown that such small particles strongly align with the local vorticity [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The problem also bears an important aspect of fluid mechanics that relates the rotational dynamics of anisotropic particles to the velocity gradient tensor in turbulence [4]. Although most studies to date have primarily focused on the dynamics of rigid particles smaller than the Kolmogorov length (η) [4,[11][12][13], some have extended this interest to rigid inertial fibers [5][6][7]9,10] as well as to flexible fibers [14][15][16][17][18][19]. Previous theoretical and numerical studies on inertialess fibers shorter than the Kolmogorov length η have shown that such small particles strongly align with the local vorticity [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The disaggregation and morphologies of rod-like particles are affected by the scale of the smallest vortexes. [63][64][65] When the particles are larger than the scale of smallest vortexes, the disaggregation and the buckling behaviors are dominant. 65 The scale of the smallest vortexes can be dened as Kolmogorov's length scale L k , which decreases as the Reynolds number increases (L k $ Re À3/4 $ (u in /n) À3/4 ).…”
Section: Aligning the Cnt Bundles In The Shear Owmentioning
confidence: 99%
“…[63][64][65] When the particles are larger than the scale of smallest vortexes, the disaggregation and the buckling behaviors are dominant. 65 The scale of the smallest vortexes can be dened as Kolmogorov's length scale L k , which decreases as the Reynolds number increases (L k $ Re À3/4 $ (u in /n) À3/4 ). 64,65 Thus, the average thickness of CNT bundles should decrease as u in increases.…”
Section: Aligning the Cnt Bundles In The Shear Owmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that, in the flexible regime, the statistics of the fibre deformations depend on the fibre length (Gay, Favier & Verhille 2018; Sulaiman et al. 2019) and that the dynamics of the deformation is given by the coherent structures of the flow (Allende, Henry & Bec 2018; Rosti et al. 2018).…”
Section: Introductionmentioning
confidence: 99%